Parallel detection of theta and respiration-coupled oscillations throughout the mouse brain - Tort, Adriano B. L.; Ponsel, Simon; Jeßberger, Jakob; Yanovsky, Yevgenij; Brankačk, Jurij; Draguhn, Andreas (Scientific reports, 2018)
Slow brain oscillations are usually coherent over long distances and thought to link distributed cell assemblies. In mice, theta (5-10 Hz) stands as one of the most studied slow rhythms. However, mice often breathe at theta frequency, and we recently reported that nasal respiration leads to local field potential (LFP) oscillations that are independent of theta. Namely, we showed respiration-coupled oscillations in the hippocampus, prelimbic cortex, and parietal cortex, suggesting that respiration could impose a global brain rhythm. Here we extend these findings by analyzing LFPs from 15 brain regions recorded simultaneously with respiration during exploration and REM sleep. We find that respiration-coupled oscillations can be detected in parallel with theta in several neocortical regions, from prefrontal to visual areas, and also in subcortical structures such as the thalamus, amygdala and ventral hippocampus. They might have escaped attention in previous studies due to the absence of respiration monitoring, the similarity with theta oscillations, and the highly variable peak frequency. We hypothesize that respiration-coupled oscillations constitute a global brain rhythm suited to entrain distributed networks into a common regime. However, whether their widespread presence reflects local network activity or is due to volume conduction remains to be determined.
Gesehen am 10.12.2024